A tracer study in a vertical flow constructed wetland treating septage - Bui, J.; Tan, Y.; Tang, Fu Ee; Ho, C. (Multi-Science Publishing Co. Ltd., 2018)
Purpose: This study aims to investigate the hydraulic behaviour of a pilot-scale, two-staged, vertical flow constructed wetland (VFCW) for septage treatment, in terms of factors such as hydraulic retention time and hydraulic loading rate and its influence on the treatment dynamics. Because of intermittent feeding mode of VFCW systems and variation in its loading, its hydraulic behaviour is highly variable and need to be understood to optimize its treatment performance. Design/methodology/approach: Tracer test were carried out using bromide ion with varying hydraulic loading rates (HLR) of 6.82 cm/d, 9.09 cm/d and 11.40 cm/d (i.e. equivalent to 75 L/d, 100L/d and 125 L/d). Tracer data is then analysed using the Residence Time Distribution (RTD) method. Findings: RTD analysis showed that the increase in HLR increases the average hydraulic retention time (HRT). Subsequently, the increase in HLR results in a lower recovery of effluent, resulting in poor productivity in treatment. The study also showed that the removal of nitrogen and organic matter improved with increasing HRT. However, observations show no correlation between HRT and total solids removal. Originality/value: A performance evaluation method (by tracer) is proposed to understand the hydraulics of flow in constructed wetlands, which has not been widely studied. Additionally, the dynamics of treatment in VFCWs treating septage may also be revealed by the tracer method. The study can be applied to any constructed wetlands designed for treatment of wastewater, septage or sludge.